2012
DOI: 10.1007/s10340-012-0425-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between adult oviposition preference and larval performance of the diamondback moth, Plutella xylostella

Abstract: Unraveling the relationship between adult oviposition preference and offspring performance is central to understanding the evolution of plant-insect interactions. In the present study, we collated previously reported data, including our own, of adult oviposition preference and offspring performance of the diamondback moth, Plutella xylostella, on various wild and cultivated crucifer plants, and did correlation analysis between the two. Intrinsic rate of increase, pupal weight and fecundity of the ensuing adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 56 publications
3
33
2
Order By: Relevance
“…As is evident from our study, pupal mass provides a good estimate of individual fecundity in many insects, including Lepidoptera (e.g. Doak 2000;Zhang et al 2012). Czypionka & Hill (2007) suggested that this relationship could be used as an index to judge the suitability of an insect (in terms of its reproductive potential) for the biological control of an invasive alien weed.…”
Section: Discussionmentioning
confidence: 91%
“…As is evident from our study, pupal mass provides a good estimate of individual fecundity in many insects, including Lepidoptera (e.g. Doak 2000;Zhang et al 2012). Czypionka & Hill (2007) suggested that this relationship could be used as an index to judge the suitability of an insect (in terms of its reproductive potential) for the biological control of an invasive alien weed.…”
Section: Discussionmentioning
confidence: 91%
“…Variation in resistance to herbivores among A. lyrata natural populations may be maintained by spatial variation in selection exerted by herbivores and other environmental factors. Additionally, the positive relationship holds mostly for intact and un-induced plants; once plants are pre-infested, this relationship is less predictable (Zhang et al, 2012). Furthermore, in a recent study, regional variation across the northwestern European range of A. lyrata in morphology and life history was significantly correlated with levels of herbivory (Vergeer & Kunin, 2011); and herbivores certainly have the potential to exert selection because leaf damage can significantly reduce fitness in A. lyrata (Puentes & Agren, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…In addition to rosette size, other unmeasured traits are likely to have influenced variation in resistance to oviposition and larval feeding by P. xylostella among young A. lyrata plants from different populations. Adult oviposition preference and larval performance tend to be positively correlated in P. xylostella across a wide range of cultivated and wild hosts (Zhang et al, 2012), although there are exceptions (Handley et al, 2005;Akiyama, 2011). The intensity of insect herbivory varies among populations in the Scandinavian range .…”
Section: Discussionmentioning
confidence: 99%
“…; Zhang et al . ). However, many other studies have revealed that adult choice and offspring performance are frequently poorly correlated (Jallow & Zalucki ; Brodbeck et al .…”
Section: Introductionmentioning
confidence: 97%